2018
DOI: 10.3390/ijms19051520
|View full text |Cite
|
Sign up to set email alerts
|

Serine Protease Inhibitor SERPINE2 Reversibly Modulates Murine Sperm Capacitation

Abstract: SERPINE2 (serpin peptidase inhibitor, clade E, member 2), predominantly expressed in the seminal vesicle, can inhibit murine sperm capacitation, suggesting its role as a sperm decapacitation factor (DF). A characteristic of DF is its ability to reverse the capacitation process. Here, we investigated whether SERPINE2 can reversibly modulate sperm capacitation. Immunocytochemical staining revealed that SERPINE2 was bound onto both capacitated and uncapacitated sperm. It reversed the increase in BSA-induced sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The fluid proteins bind to the surface of sperm to modulate sperm capacitation. Previous studies have unveiled seminal plasma DFs such as SVS2 4 and SERPINE2 5 that can reverse capacitation to prevent sperm from premature capacitation. SPINKL can prevent sperm capacitation but cannot reverse capacitation 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluid proteins bind to the surface of sperm to modulate sperm capacitation. Previous studies have unveiled seminal plasma DFs such as SVS2 4 and SERPINE2 5 that can reverse capacitation to prevent sperm from premature capacitation. SPINKL can prevent sperm capacitation but cannot reverse capacitation 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The ejaculated sperm must reside in the female reproductive tract for a period of time and undergo capacitation to gain the ability to fertilize an egg 1,2 . Capacitation can be reversed by decapacitation factors (DFs), which are present in the seminal plasma 3 and can bind to sperm to prevent prematurely capacitated sperm from losing its fertilization ability 4,5 . When spermatozoa enter the oviduct, DFs are removed from the sperm plasma membrane before or during the capacitation process 4,5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that SERPINE2 could inhibit sperm capacitation by blocking the cholesterol outflow of sperm plasma membranes and inhibiting the increase in the level of tyrosine phosphorylation in rat sperm protein [38]. Li et al further confirmed that SERPINE2 could reversibly regulate mouse sperm from the state of capacitated to incapacitated [39]. Results indicated that capacitation inducers (such as BSA [36], cAMP analogs [40], and methyl-β-cyclodextrin [41]) or SERPINE2 inhibitor need to be added in buck sperm cryoprotectants for AI improvement.…”
Section: Major Spermatozoa Proteins In Bucksmentioning
confidence: 95%
“…Sperm count and motility assay. The process of the sperm motility assay was modified from previous studies 61,62 . The rat cauda epididymis was punctured by scissors and 2 μl semen was mixed with 2 ml Medium 199 culture medium (containing 1% BSA and 1 g/L glucose).…”
Section: Protein Preparation and Western Blot Analysis Total Cell Anmentioning
confidence: 99%